The Acculturation Dynamics of the Sekaten Tradition in Modern Indonesia - Abdul Karim; Moch. Khafidz Fuad Raya (Jurnal Dialog, 2022)
This article examines the socio-religious dynamics behind the traditional sekaten held by two large palaces (keraton) of Javanese (Surakarta keraton and Yogyakarta keraton). This phenomenon is unique. Sekaten is a local traditional cultural performance, which combines Islam with Javanese culture. The current dynamics of acculturation make tourism opportunities. Using a qualitative approach and historical and ethnographic methods, data were collected through in-depth observations during the sekaten celebration at the Yogyakarta Palace. The results indicate that in the past the sekaten tradition functioned as a ‘religious institution’, which made the Surakarta palace and the Yogyakarta palace the two symbols of the strongest Islamic empire in Java. This research contributes that the local Islamic tradition in the past has undergone a paradigm shift, although the tradition has been preserved until the modern era. In the modern context, local cultural traditions have changed and created economic value through cultural tourism destinations supported by local governments. Keywords: sekaten, local traditions, Islam, dynamics, commodities